Elemental Concentrations in the Surface Sediments Collected from the Straits of Malacca: 2004 Sampling Cruise - C. K. Yap (Institute of Advanced Engineering and Science, 2014)
In this study, surface sediments from four geographical sampling sites in the Straits of Malacca (three near the northern part and one near the central part) were collected between February and March 2004 and they were analyzed for 35 elements by using an Inductively Coupled Plasma Mass Spectrometry (7 elements) and an Instrumental Neutron Activation Analysis (28 elements). It was found that one site at the northern part had highest levels of 23 elements out of 35. This indicated that the sampling site located at the northern part had received anthropogenic inputs due to shipping activities. However, illegal dumpings and other unidentified sources could not be rule out. In general, As, Cd, Cr, Cu, Pb and Zn have low potential to cause adverse effects on biota except for Ni that a biological effect could affect some benthic species occasionally, as compared to the Interim Sediment Quality Values. Therefore, this study provided an evidence that high elemental concentrations is plausibly due to shipping activities since the Straits of Malacca is the busiest shipping lane in this region.